Flight Capital As a Portfolio Choice. - Collier, P; Hoeffler, A; Pattillo, C (2001)
This article sets flight capital in the context of portfolio choice, focusing on the proportion of private wealth that is held abroad. There are large regional differences in this proportion, ranging from 5 percent in South Asia to 40 percent in Africa. The authors explain cross-country differences in portfolio choice using variables that proxy differences in the risk-adjusted rate of return on capital. They apply the results to three policy issues: how the East Asian crisis affected domestic capital outflows; the effect of the International Monetary Fund-World Bank debt relief initiative for heavily indebted poor countries on capital repatriation; and why so much of Africa's private wealth is held outside the continent.